2007
DOI: 10.1097/01.ta.0000229789.18211.85
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic Imaging Guides of the Posterior Pelvis Pertaining to Iliosacral Screw Placement

Abstract: Use of predetermined angles for inlet and outlet views may not provide optimal visualization of relevant bony landmarks during iliosacral screw insertion. Because of variable sacral morphologies and lumbosacral lordosis, we propose using inherent landmarks to help visualize important landmarks during screw placement. Altering the fluoroscopic angle to superimpose the anterior S1 and S2 alar opacities allows the best visualization of the anterior boundary of the S1 ala. The superior bony surface of the S1 foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 22 publications
1
51
5
Order By: Relevance
“…We measured the length of an osseous corridor along the safe zone axis of 10 mm in diameter. Ten millimeters was chosen to provide 1 to 2 mm of circumference around a 6.3 to 8-mm-diameter screw, and has been previously established as a reasonably ''safe''-diameter corridor by experienced surgeons 4,29,37 . The smallest cross-sectional area that we measured in a first sacral osseous corridor was 206 mm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the length of an osseous corridor along the safe zone axis of 10 mm in diameter. Ten millimeters was chosen to provide 1 to 2 mm of circumference around a 6.3 to 8-mm-diameter screw, and has been previously established as a reasonably ''safe''-diameter corridor by experienced surgeons 4,29,37 . The smallest cross-sectional area that we measured in a first sacral osseous corridor was 206 mm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The maximum length of iliosacral screw that could be used safely was measured by the longest line that could be drawn along the axis of the osseous corridor with no less than 5 mm of distance to the cortex on either side of the line in the coronal reformats. A 10-mmdiameter corridor perpendicular to the axis of the safe zone was chosen as a conservative size for passage of an iliosacral screw 29,37 . The maximum length of this safe corridor was determined for the first and second sacral segments, and cluster analysis was used to test the hypothesis that pelves would group according to these variables.…”
Section: Quantification Of the Osseous Safe Corridormentioning
confidence: 99%
“…Whereas some reports have indicated that the technique can be applied safely, 13,14,23 the proximity of the spinal canal, nerve roots, and pelvic vessels can result in significant complications, 15 leading some authors to conclude that the procedure may be more safely performed with image-based navigation. 17,18 A previous report by Sciubba, et al 16 described percutaneous placement of an transiliosacral rod in combination with a methylmethacrylate sacroplasty for an insufficiency fracture.…”
mentioning
confidence: 99%
“…The drawback of transsacral screw fixation is the difficult placement owing to the individual variable three-dimensional anatomic shape of the sacrum (sacral dysmorphism), with several neurovascular structures in close proximity to the osseous boundary (S1 corridor: L4 and L5 nerve route and internal iliac vessels above and in front of the sacral alar region; S1 nerve route and the residual nerve pairs in the spinal canal below and posterior; S2 corridor: S1 foramen with its nerve route above and S2 foramen with its nerve route below) [3,7,34]. Furthermore there is limited ability to see all relevant bony structures on the intraoperative two-dimensional fluoroscopic images [7,22,29,31,40]. The corridor for the oblique sacroiliac screw placement in the first vertebra has been investigated in different biomorphometric studies [2,7,8,16], but data for transverse transsacral screw placement at the level of S1 and S2 are limited owing to the small size of study groups, different exclusion criteria, or measurement techniques [11,22,23,37,39].…”
Section: Introductionmentioning
confidence: 99%